Post COVID Mucormycosis Prevention With Oro-Nasal Application of Povidone Iodine (Pvp-I) - Arefin, Mostafa Kamal; Khan, Mala; Rumi, SK Nurul Fattah; Islam, Md Nazmul; Talukder, Debesh Chandra; Osmani, Husne Qumer; Hossain, Mohammod Delwar; Arafat, Muhammad Shaharior; Kaiser, Ahsanul; Samad, Md Sazzad; Uddin, Md Baha; Chowdhury, Joybaer Anam; et al. (Journal of Dhaka Medical College, 2023)
In March 2020 WHO declared COVID-19 as pandemic while April 2021 Indian authority concede to declare a significantly increased incidence of “Black Fungus” among the COVID-19 patients. The primary route of infection for Mucormycosis or fungal infection following COVID-19 is inhalation or ingestion resulting accumulation of the agents in nose, para-nasal sinuses and mouth. The spores of black fungus intrude neural and vascular structure, which cause mucosal necrosis due to thrombosis in vasculature. The extension of the disease then increases through further destruction of bones of para-nasal sinus as well as neural and vascular route dissemination. We thought about removing, neutralizing or destroying the culprit fungi from its route of entry zone, i.e. nose and mouth. Povidone Iodine (PVP-I) is a microbicidal agent having effective fungicidal as well as virucidal and bactericidal property. PVP-I can be used in both oral and nasal cavity safely. Efficacy and safety of PVP-I is proved in nose in case of COVID-19. PVP-I is proved effective against different fungi at different concentration at different site. So, we recommend Povidone Iodine nasal spray or irrigation and mouthwash for gargling for these vulnerable group of patients in large scale to prevent post-COVID mucormycosis or fungal infection. J Dhaka Med Coll. 2021; 30(2) : 176-179